Use of Intracytoplasmic Sperm Injection (ICSI) to generate transgenic animals - Moisyadi, Stefan (2008)
Even though Intracytoplasmic Sperm Injection (ICSI) has been widely used for the production of offspring in human infertility clinics and in reproductive research laboratories using mice, many researchers engaged in animal transgenesis still consider it somewhat cumbersome. The greatest advantage of ICSI-mediated transgenesis is that it allows introduction of very large DNA transgenes (e.g., yeast artificial chromosomes), with relatively high efficiency into the genomes of hosts, as compared to pronuclear injection. Recently, we have developed an active form of ICSI-Tr with fresh sperm utilizing transposons. The transgenic efficiencies rival all transgenic techniques except that of lentiviral methods.